2017
DOI: 10.1097/md.0000000000008059
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different anticoagulant drugs on the prevention of complications in patients after arthroplasty

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…Apixaban is a direct inhibitor of factor Xa (free as well as clot-bound); it selectively and reversibly inhibits the conversion of prothrombin into thrombin, which is the final step for the formation of a clot; it was also reported to be associated with fewer chances of bleeding postoperatively in a meta-analysis that is also in accordance with the present findings [20,21]. We prescribed Rivaroxaban 10 mg as a once-daily oral regime for four weeks for DVT prophylaxis to our patients postoperatively, which proved more convenient to the patient in comparison with apixaban, which is a twice-daily dose.…”
Section: Discussionsupporting
confidence: 90%
“…Apixaban is a direct inhibitor of factor Xa (free as well as clot-bound); it selectively and reversibly inhibits the conversion of prothrombin into thrombin, which is the final step for the formation of a clot; it was also reported to be associated with fewer chances of bleeding postoperatively in a meta-analysis that is also in accordance with the present findings [20,21]. We prescribed Rivaroxaban 10 mg as a once-daily oral regime for four weeks for DVT prophylaxis to our patients postoperatively, which proved more convenient to the patient in comparison with apixaban, which is a twice-daily dose.…”
Section: Discussionsupporting
confidence: 90%
“…Three major studies of safety comparisons were identified in the literature: LMWH versus ASA 248 , non-vitamin-K oral anticoagulants (NOAC, including direct factor Xa inhibitors and other, such as rivaroxaban, dabigatran, apixaban, ximelagatran, etc.) versus LMWH 249-262 or ASA 263-265 , and NOAC of different groups comparing to each other 252,266 . Bleeding rates are not always reported, and bleeding risks may be used as the surrogate.…”
Section: - Which Vte Prophylactic Agent Used In Patients Undergoing T...mentioning
confidence: 99%
“…NOAC comparisons report slightly different bleeding rates for each agent against LMWH (usually enoxaparin) and among them. A synthesis includes: major bleeding in 1.4% (220 mg) or 1.1% (150 mg) vs. 1.4% (3 trials and 8,135 patients in dabigatran vs enoxaparin 251 ,); major or non-major, clinically relevant bleeding RR vs. enoxaparin of 1.52 (ribaroxaban), 0.34 (betrixaban), 0.88 (apixaban), 0.85 (darexaban), 1.30 (edoxaban) 250 ; better preventive effects on bleeding with apixaban 252 ; RR of major bleeding of oral direct factor Xa inhibitors vs. enoxaparin, 1.27 (5 trials, 12,184 patients with THA) and 0.94 (5 trials, 13,169 patients with TKA) being non significantly different from enoxaparin 253 ; less bleeding (and less efficacy) of enoxaparin vs. immediately postop ximegalatran with hip odds ratio (OR) = 0.30 and knee OR = 0.71 (6 trials, 10,051 THA or TKA patients) 254 ; compared to enoxaparin, the RR of clinically significant risk of bleeding was higher with rivaroxaban (RR = 1.25), similar with dabigatran (RR = 1.12) and lower with apixaban (RR = 0.82) in a meta-analysis of 16 trials, 38,747 THA or TKA patients 256 ; compared with dabigatran, enoxaparin similarly efficacious and similar risk of bleeding (OR = 0.90), while compared with rivaroxaban, enoxaparin less efficacious but lower risk of bleeding (OR = 0.79) in a meta-analysis with 6 trials, 18,405 THA or TKA patients 257 ; in a network meta-analysis with 19 trials and 43,838 THA or TKA patients, OR were also calculated against enoxaparin 30 mg twice a day ( bis in die [bid]) or 40 mg daily, and bleeding (major/non-major clinically relevant) was significantly increased for fondaparinux (vs. 40 mg daily, OR = 0.67) and rivaroxaban (vs. 40 mg daily, OR = 0.77) 258 , while apixaban as the comparator (2.5 mg bid) showed increased bleeding with enoxaparin 30 mg bid (OR = 0.75), dabigatran (OR = 0.73), fondaparinux (OR = 0.56), and rivaroxaban (OR = 0.65); a meta-analysis with 21 randomized control trials (RCT) 259 produced major bleeding rates with enoxaparin of 1.32%, dabigatran 1.25%, rivaroxaban 2.02%, apixaban 0.70%, ximegalatran 0.93%; a pooled analysis of 2 RCT with 8,464 THA or TKA patients comparing apixaban and enoxaparin showed a major bleeding rate of 0.7% and 0.8%, but when non-major clinically relevant bleeding was summed, the rates were 4.4% for apixaban and 4.9% for enoxaparin 260 . As a summary, major bleeding rates for enoxaparin were reported from 0.8 to 1.3%, for dabigatran 1.1 to 1.4%, for apixaban around 0.7, for rivaroxaban around 2%.…”
Section: - Which Vte Prophylactic Agent Used In Patients Undergoing T...mentioning
confidence: 99%
“…Venous thromboembolism (VTE) (including deep vein thrombosis [DVT] and pulmonary embolism [PE]) remains one of the major causes of morbidity, mortality, and costs in total hip and knee arthroplasty (THA/TKA) 1 . Compliance with clinical practice guidelines (CPG) has been inconsistent due to concerns with the quality and recency of evidence, the relevance of symptomatic versus asymptomatic VTE, and the need to balance the risks and benefits of VTE prophylaxis against the risk of bleeding and surgical site infection 2 4 .…”
Section: Introductionmentioning
confidence: 99%